Redox Mechanism of Reactive Oxygen Species in Exercise - He, Feng; Li, Juan; Liu, Zewen; Chuang, Chia-Chen; Yang, Wenge; Zuo, Li (Frontiers in Physiology, 2016)
It is well known that regular exercise benefits health. However, unaccustomed and/or exhaustive exercise can generate excessive reactive oxygen species (ROS), leading to oxidative stress-related tissue damage and impaired muscle contractility. ROS are produced in both aerobic and anaerobic exercise. Although mitochondria, NADPH oxidases and xanthine oxidase have all been identified as contributors to ROS production, the exact redox mechanisms underlying exercise-induced oxidative stress remain elusive. Interestingly, moderate exposure to ROS is necessary to induce the body’s adaptive responses such as the activation of antioxidant defense mechanisms. Dietary antioxidant manipulation can also reduce ROS levels and muscle fatigue, as well as enhance exercise recovery. To elucidate the complex role of ROS in exercise, this article updates on new findings of ROS origins within skeletal muscles associated with various types of exercises such as endurance, sprint and mountain climbing, corresponding antioxidant defense systems as well as dietary manipulation against damage caused by ROS.